2011
DOI: 10.1021/jp205349e
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Structures and Electronic Properties of 1,4-Phenylene Diisocyanide on the Au(111) Surface

Abstract: The adsorption structures and electronic properties of 1,4-phenylene diisocyanide (PDI) on a Au(111) surface have been studied using temperature programmed desorption (TPD), two-photon photoemission (2PPE), and scanning tunneling microscopy (STM). As deposited at 95 K, PDI molecules form disordered islands and short one-dimensional chains on Au(111) terraces. The work function decreases with increasing PDI coverage, and an occupied electronic state appears at 0.88 eV below the Fermi level. Annealing to 300 K c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Zhou et al predicted by DFT calculations that vertically adsorbed PDI on Au has the HOMO and LUMO states at 0.7 and 3 eV above the Fermi level of the metal (E F ) that can be modified by changing the surface coverage. 51 This means that an induced charge-transfer effect from the metal to the adsorbate may occur by changing the excitation laser wavelength to fit the 3 eV transition energy between the PDI LUMO and the Fermi level. Furthermore, Li et al also predicted that the energetic gap between the LUMO and E F can change when varying the surface coverage.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Zhou et al predicted by DFT calculations that vertically adsorbed PDI on Au has the HOMO and LUMO states at 0.7 and 3 eV above the Fermi level of the metal (E F ) that can be modified by changing the surface coverage. 51 This means that an induced charge-transfer effect from the metal to the adsorbate may occur by changing the excitation laser wavelength to fit the 3 eV transition energy between the PDI LUMO and the Fermi level. Furthermore, Li et al also predicted that the energetic gap between the LUMO and E F can change when varying the surface coverage.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…6 Spectroscopic studies of Au-PDI oligomers on Au(111) show that the HOMO of the oligomer lies B0.88 eV below the Fermi level, with a LUMO B3.32 eV above it, consistent with a HOMO tunnelling barrier. 17 More recent experiments found a barrier height of 0.19 AE 0.02 eV (ref. 36) where the difference from previous results was ascribed to different numbers of PDI molecules in the contact.…”
Section: à2mentioning
confidence: 98%
“…[15][16][17] The relatively short (B1.1 nm) repeat distance between gold atoms in the oligomer suggests the possibility of being able to chemically bond between gold nanoparticles with various separations by incorporating a number of repeat units until the gap is bridged. PDI has been previously proposed as a prototypical molecular electronic component, 4,6,[18][19][20][21] and theory suggests that PDI is a suitable candidate for device applications.…”
mentioning
confidence: 99%
“…This is longer than that observed for PDI chains on Au(111), 11.7±0.2 Å, by approximately the length of an extra phenyl ring (see Figure 3). 17,18,24 The correlation between the monomer length and molecular dimensions supports an adsorption geometry in which BPDI molecules lie parallel (or nearly so) to the surface. Since abutting -NC terminal groups are not likely to be chemically linked, diisocyanide chain formation would require a common surface binding site for both terminal -NC groups.…”
Section: A Adsorption Structuresmentioning
confidence: 76%
“…[19][20][21][22][23] In a related study, Zhou et al examined the temperaturedependent surface morphology and electronic structure of PDI/Au(111) surfaces using a combination of variable-temperature STM and two-photon photoemission (2PPE) spectroscopy. 24 It was found that the PDI molecules vapor-deposited at low temperature formed disordered islands or very short chain segments at step edges. As the surface was heated to room temperature, the disordered islands disappeared and the PDI molecules self-organized into 1D molecular chains.…”
Section: Introductionmentioning
confidence: 99%